Mobile Application for Child Tracker - Mohamad Idris, ‘Ainor Liyana (IRC, 2019)
Most cell phones are furnished with location services functions, enabling us to get the gadget’s geographic location in real time. The intended solution utilizes the location services offered by cell phone since most of the children age between 8 to 17 years of age carry a cell phone. In 2017, total of 1803 children under 18 years old were reported missing. 979 of 1803 were found while the rest are still missing. In abducting cases, it is regularly said that locating the child within 24 hours gives them the absolute best of survival. A GPS tracking application can trim those hours down to minutes. The main deliverables of this study are to prevent a kidnapping incident by alerting the parents regarding their child’s location. A child tracker has been developed using Android Studio and Google Map as the mapping platform.